Analisis Kinerja Protokol Routing Fisheye State Routing (FSR) dan Ad-Hoc On Demand Multipath Distance Vector (AOMDV) pada Mobile Ad-Hoc Network - Bagos Wahyu Suprayugi; Rakhmadhany Primananda; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MANET is a set of mobile nodes that exchanges the information from the source to destination nodes by utilizing wireless networks. Each node in MANET can apply as a host or router, wherein each node can determine the path to other nodes on a network. Reactive and proactive protocols are the types of routing protocols which most often used in the scope of MANET network. In this research, researcher used a scenario of variations in the number of nodes, variations in packet size and node speed that would be simulated using Network 2.35 Simulator in MANET areas. The Quality of Service (QoS) parameters used in this study are end to end delay, routing overhead, packet delivery ratio and energy consumption. Based on the result of simulation, indicate that AOMDV has better performance on end to end delay and packet delivery ratio parameters, while FSR has better grade on routing overhead and energy consumption. The average grade of the AOMDV end to end delay and packet delivery ratio is 475,941 s and 38,246%, and the grade of routing overhead and FSR energy consumption are 84151.4 packet and 591.6 joules.